Parents' perspective in providing support to their children when using learning platforms during distance learning in light of Corona pandemic in Jordan - Al-kura`an, Reham Ahmad (Journal of Educational and Psychological Sciences, 2022)
This study aimed to identify the parents' perspective in providing support to their children when using learning platforms during distance learning in light of the Corona pandemic. The study used the descriptive, analytical approach and the study sample consisted of (140) parents who were randomly selected from the teachers and parents of the public schools in Zarqa 2nd District.To achieve the objectives of the study, the researcher prepared a questionnaire as a tool to collect data from the study sample. After verifying the validity and reliability of the tool, the study concluded a medium degree in the parents' perspective in providing support to their children when using the learning platforms during distance learning in light of the Corona pandemic and no statistically significant differences at sig. (0.05≥α) in the parents' perspective in providing support to their children when using the learning platforms during distance learning in light of Corona pandemic due to the variables of (gender, age, qualification, job, and monthly income). Based on the conclusions, the study recommends the need for qualifying the parents with the distance education and the need for holding training courses to all people involved in education planning in the field of distance education management.
Keywords: Parents' perspective; Distance learning; learning platform; Corona pandemic